2015
DOI: 10.1523/jneurosci.0815-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Direction Modulates the Relation between Neural Responses to Faces and Visual Awareness

Abstract: Gaze direction and especially direct gaze is a powerful nonverbal cue that plays an important role in social interactions. Here we studied the neural mechanisms underlying the privileged access of direct gaze to visual awareness. We performed functional magnetic resonance imaging in healthy human volunteers who were exposed to faces with direct or averted gaze under continuous flash suppression, thereby manipulating their awareness of the faces. A gaze processing network comprising fusiform face area (FFA), su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…In sum, these findings fit the fast‐track modulator model, which proposed the involvement of a subcortical pathway for direct eye gaze detection (but see Mormann et al, ). It is also consistent with a claim that direct gaze would be preferentially processed in a rather involuntary manner (for a similar conclusion in other studies using different experimental manipulations, see Madipakkam, Rothkirch, Guggenmos, Heinz, & Sterzer, ; Stein, Senju, Peelen, & Sterzer, ; Yokoyama, Noguchi, & Kita, ; Yokoyama et al, ).…”
Section: Fast‐track Modulator Modelsupporting
confidence: 90%
“…In sum, these findings fit the fast‐track modulator model, which proposed the involvement of a subcortical pathway for direct eye gaze detection (but see Mormann et al, ). It is also consistent with a claim that direct gaze would be preferentially processed in a rather involuntary manner (for a similar conclusion in other studies using different experimental manipulations, see Madipakkam, Rothkirch, Guggenmos, Heinz, & Sterzer, ; Stein, Senju, Peelen, & Sterzer, ; Yokoyama, Noguchi, & Kita, ; Yokoyama et al, ).…”
Section: Fast‐track Modulator Modelsupporting
confidence: 90%
“…In an fMRI study, Madipakkam, Rothkirch, Guggenmos, Heinz, and Sterzer (2015) found significantly stronger response to the visible faces with direct gaze in the FFA and IPS and close to significant stronger response to the visible faces with direct gaze in area STS, but not in the amygdala. In the invisible condition, Madipakkam et al (2015) found significant stronger amygdala and STS and close to significant stronger FFA response to the face with averted gaze. These results are in accordance with Jiang and He's (2006) and Sterzer et al's (2009) results.…”
Section: Neural Correlates Of Conscious and Nonconscious Face And Facmentioning
confidence: 88%
“…For instance, subliminal face stimuli elicited weaker neural activities in the prefrontal regions and the fusiform face area compared to supraliminal stimuli ( Leopold and Logothetis, 1996 ; Tong et al, 1998 ; Jiang and He, 2006 ). In contrast, regions in the subcortical pathway have been demonstrated to respond to eye contact even in the absence of visual awareness ( Madipakkam et al, 2015 ; Rothkirch et al, 2015 ). Thus, the effect of subliminal eye contact may mainly result from basic, reflective processing via the subcortical pathway, while the modulation from sociocultural norms may be weakened due to the limited access to certain cortical regions, as found in implicit social attitudes tasks ( Greenwald et al, 1998 ; Nosek et al, 2002 ; Kiefer and Sekaquaptewa, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of eye contact, it is not surprising that eye contact can be processed at a subliminal level to modulate basic cognitive processes. For instance, subliminally presented eye contact facilitates visual awareness compared to averted gaze in interocular suppression, and is more capable of capturing attention as well as attracting eye movement than averted gaze ( Stein et al, 2011 ; Chen and Yeh, 2012 ; Madipakkam et al, 2015 ). However, there is less investigation regarding whether and how eye contact modulates social cognition when the eye contact was presented without visual awareness.…”
Section: Introductionmentioning
confidence: 99%